اشكالية درس البلاغة العربية في الموءسسة التعليمية الماليزية (Ishkaliyah darsu balaghah al-a’rabiah fil muassah at-ta'līmiyyah al-maliziah) - Muaffak Abdullah Al-Qusyairi (Penerbit Universiti Kebangsaan Malaysia, 2012)
THe main aim of this paper is to disclose the most important problems that may effect adversely the process of teaching and learning of Arabic rhetoric (elocution in Malaysian institute of advance learning from two main axes namely the content of Arabic rhetoric and the methods of teaching these contents. In related issues the historical development of the Arabic rhetoric written styles were dealt with. It is a general agrement that Arabic rhetoric is an art in its nature and the main purpose of its teaching is to enable the learner to know the rules of its as it set by the Arabic rhetoric pioneers in clasical Arabic and to apply these rules correctly in their written and soken language versions. In other words, the adoption of funtional approach in the process of teaching and learning of these rhetoric rules as atool not as an aims in itself. Finally, the paper may suggest aproper remedy to overcome these problem which may hinder the functional method of teaching Arabic rhetoric in Malaysian context.